LINGUOCULTUROLOGY AND ITS STUDY IN WORLD LINGUISTICS (Web of Teachers: Inderscience Research, 2025)
This article outlines the scientific foundations of linguoculturology and its focus on studying language as a cultural phenomenon. It also discusses the connection of linguoculturological research with other branches of linguistics and the close relationship between language and culture.